The effects of self-disclosure and therapist/client-gender dyads on the perceived working alliance - Stevens, Paul L. (Kansas State University, 2008)
This study examined the effects of types of therapist disclosure and their interaction with various combinations of observer, therapist, and client gender-dyads on observer ratings of the working alliance. Participants were 357 undergraduate students (60.2% women) from two Midwestern universities who were randomly assigned to one of 12 conditions. Each condition required students to read one of 12 printed scenarios differentiated by all possible combinations of three types of therapist self-disclosure (similar, dissimilar, no disclosure), two levels of therapist gender, and two levels of client gender. Students rated the scenarios on the perceived working alliance between the therapist and the client, using the 36-item Working Alliance Inventory-Observer (WAI-O). A 2 (student sex) x 2 (therapist sex) x 2 (client sex) x 3 (disclosure type) ANOVA revealed no significant effects on the WAI-O total scale score. In addition, no main effects or interactions were found on WAI-O total scale when male and female student scores were pooled. A 2 x 2 x 2 x 3 MANOVA performed on the WAI-O subscales indicated female observers perceived a stronger client-therapist bond for similar than dissimilar disclosures with male clients. Female observers rated male clients with a stronger bond than female clients, but only in the similar disclosure condition. A main effect was also found for observer sex on the Task and Bond subscales. Although this study did not find gender of the observer, type of therapist disclosure, and the gender of the therapist and their client to influence overall working alliance ratings, results suggest that these factors have an impact on female observer ratings of the bond and task agreement between the therapist and their client. Specifically, two findings emerged: (a) women, not men, observed a stronger bond for male client recipients of similar versus dissimilar disclosure; (b) women, not men observed a stronger bond for male client versus female recipients of a therapist's similar disclosure. Results are discussed in terms of disclosure and gender research.
Keywords: self-disclosure; working alliance; gender; Education, Guidance and Counseling (0519)